Quantum Imaging for Medical and Industrial Applications - Mutmainnah Mutmainnah; Khazali Fahmi; Raditya Faradina Pratiwi; Adhi Kusumadjati (Journal of Tecnologia Quantica, 2024)
Quantum imaging is a quantum principle-based imaging technology that shows great potential in medical and industrial applications. This study was conducted to evaluate the advantages of quantum imaging compared to conventional technology in terms of energy efficiency, image resolution, and detection accuracy. The research design uses an experimental approach with testing on biological networks for medical applications and metal materials for industrial applications. The data was quantitatively analyzed to measure energy efficiency, resolution, and accuracy and compared with the results of conventional technologies. The results show that quantum imaging is able to improve energy efficiency by up to 35%, produce an image resolution of 200 nm, and achieve a detection accuracy of 95% in medical applications and 92% in industrial applications. In medical applications, this technology enables early diagnosis of diseases through the detection of molecular changes, while in industrial applications, it is capable of detecting microcracks that are difficult to see. This advantage shows that quantum imaging can be an innovative solution for modern imaging needs. The conclusion of this study is that quantum imaging has the potential to replace conventional imaging technology with advantages in efficiency, resolution, and accuracy. Further research is needed to overcome the limitations of large-scale implementation of this technology and develop more practical devices.